2007
DOI: 10.1093/jn/137.1.183s
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation, Cancer, and Targets of Ginseng

Abstract: Chronic inflammation is associated with a high cancer risk. At the molecular level, free radicals and aldehydes, produced during chronic inflammation, can induce deleterious gene mutation and posttranslational modifications of key cancer-related proteins. Other products of inflammation, including cytokines, growth factors, and transcription factors such as nuclear factor kappaB, control the expression of cancer genes (e.g., suppressor genes and oncogenes) and key inflammatory enzymes such as inducible nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(140 citation statements)
references
References 34 publications
3
136
0
1
Order By: Relevance
“…Modern pharmacological studies have shown that Ginseng Radix and its active constituents have antitumor, antioxidant, immunomodulation, anti-ulcer, anti-adhesive, antioxidant, hepatoprotective, hypoglycemic activities, and so on (17). They have been proposed to have a chemopreventive effect on lung, gastric, liver, pancreas, and colon cancers and so on in cells, animals or humans (17)(18)(19)). An epidemiological study indicated that patients taking ginseng had a 50% lower risk of cancer recurrence compared to patients not taking ginseng (12).…”
Section: Ginseng Radixmentioning
confidence: 99%
“…Modern pharmacological studies have shown that Ginseng Radix and its active constituents have antitumor, antioxidant, immunomodulation, anti-ulcer, anti-adhesive, antioxidant, hepatoprotective, hypoglycemic activities, and so on (17). They have been proposed to have a chemopreventive effect on lung, gastric, liver, pancreas, and colon cancers and so on in cells, animals or humans (17)(18)(19)). An epidemiological study indicated that patients taking ginseng had a 50% lower risk of cancer recurrence compared to patients not taking ginseng (12).…”
Section: Ginseng Radixmentioning
confidence: 99%
“…Ginseng extract significantly decreases DNA synthesis and increases the rate of DNA excision repair synthesis in V79 Chinese hamster lung cells (Rhee et al, 1991), in addition to its ability to attenuate inflammation-mediated carcinogenesis (Hofseth and Wargovich, 2007). These mechanisms can reduce tumor growth and improve the prognosis in cancer patients (Wang et al, 2007).…”
Section: Antigenotoxic Effects Of Panax Ginseng 949mentioning
confidence: 99%
“…Studies have shown that ginseng plays a role in inflammation reduction and thereby reduces the risk of cancer (Keum et al, 2003;Hofseth and Wargovich 2007). In another study it was shown that the anticancer effect of steamed ginseng is enhanced with antioxidants .…”
Section: Effect Of Ginseng On Colorectal Cancermentioning
confidence: 99%